2021
DOI: 10.3390/f12111470
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Effects of Forest Thinning on N Mineralization in a Semi-Arid Aleppo Pine Forest

Abstract: In order to assess the sustainability of silvicultural treatments in semiarid forests, it is necessary to know how they affect the nutrient dynamics in the forest. The objective of this paper is to study the effects of silvicultural treatments on the net N mineralization and the available mineral N content in the soil after 13 years following forest clearings. The treatments were carried out following a randomized block design, with four treatments and two blocks. The distance between the two blocks was less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…It is important to remark that these general results had a high number of sources of variability, and they also considered different data sources. When comparing our results to other studies with similarities in terms of thinning (intensity and time elapsed), forest structure and composition, and environmental conditions, TOC for the 0-10 cm soil depth interval was not significantly enhanced 13 years after thinning (light and heavy thinning interventions) in an Aleppo pine plantation very similar to ours [29]. In addition, other thinning experiments, conducted in the Mediterranean area for Pinus pinaster Ait.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is important to remark that these general results had a high number of sources of variability, and they also considered different data sources. When comparing our results to other studies with similarities in terms of thinning (intensity and time elapsed), forest structure and composition, and environmental conditions, TOC for the 0-10 cm soil depth interval was not significantly enhanced 13 years after thinning (light and heavy thinning interventions) in an Aleppo pine plantation very similar to ours [29]. In addition, other thinning experiments, conducted in the Mediterranean area for Pinus pinaster Ait.…”
Section: Discussionsupporting
confidence: 87%
“…We obtained mean values of 7094, 4815, and 2650 kg ha −1 (1.71, 1.10, and 0.65%) for the SOC fraction for the 0-10, 10-20, and 20-30 cm soil depth intervals, while a mean value of 35,160 kg ha −1 (4.7%) was found when considering total organic carbon (TOC) for the 0-10 cm soil depth interval. These values are in the range of other studies on Pinus species growing under Mediterranean conditions; for instance, Bautista et al [29] reported a range of 1.1-5.4% for TOC in a Pinus halepensis plantation with different thinning treatments, while a mean value of 4.84% for SOC was reported in a plot with an intermediate forest cover dominated by Pinus pinaster [33]. Thirteen years after thinning, all the organic carbon fractions analyzed decreased with thinning intensity, but significant differences were not observed between the experimental plots.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…With regard to the latter, forest soils are important carbon (C) stores in different pools; 45% of forest C is found as soil organic matter, and 11% as dead wood and litter [23]. It has been described that forest thinning can affect nutrient mineralisation rates in the forest floor and mineral soil, soil organic carbon (SOC) content, and also labile SOC fractions [24,25]. Many studies have focused on the effects of thinning on SOC [26], but the results are still controversial.…”
Section: Introductionmentioning
confidence: 99%